Optimization of Glutathione S-Transferase in the Sera of Young Female Iraqi Patients with Diabetes Mellitus Type1 (Baghdad Science Journal, 2015)
This study was attempted to determine optimum conditions, for Glutathione s-Transferase enzyme, in sera of three groups diabetic patients type1 depending on duration of disease without complications compared with control group. The aim of this study was to find optimum conditions were determined such as (pH, Substrate Concentration, Temperature, Incubation time, Enzyme concentration, and effect of(0.15M)(0.25M) of mono divalent compounds). And to find the kinetics parameters in the three groups of diabetic patients when compared with control. It was found optimum pH(8.5,4.5,2.5,6.5).Temperatures(20cº,40cº,50cº,30cº). Incubation times (7min, 4min, 4min, 5min) substrate concentrations (12µl, 10µl, 5µl, 10µl) enzyme concentrations by enzyme volumes (125µl, 100µl, 75µl, 100µl) for group one, two, three and control group respectively., The maximum activity was presence in mono valent compounds were found in NaCl while in divalent compounds the maximum activity was presence CuSO4 more than the other compounds. By using line weaver –Burk plot we estimate the three values of Km and three values Vmax for the three groups of diabetic patients and control. which enhance our result that there are confirm three isoenzymes for Glutathione –S- transferase.